LINC-13. THE STATE OF PEDIATRIC NEURO-ONCOLOGY IN ARMENIA. (4th December 2020) - Bardakhchyan, Samvel; Tananyan, Armen; Danielyan, Samvel; Arakelyan, Jemma; Mkhitaryan, Sergo; Bedirian, Karen; Safaryan, Liana; Arustamyan, Mikayel; Tamamyan, Gevorg
Abstract: BACKGROUND: Every year in Armenia we have approximately 80–90 new pediatric cancer cases from which 10–15 are brain tumors (PBT). Here we try to summarize the current state of pediatric neuro-oncology in Armenia. DISCUSSION: In Armenia pediatric neuro-oncology is still in its first steps. Surgical treatment of PBTs is performed only in one medical center – "Sourb Astvatsamayr" Medical Center, with 7 practicing pediatric neurosurgeons. Radiation therapy service with two linear accelerators is located at the "National Oncology Center", however there are no dedicated pediatric radiation neuro-oncologists, and 2 specialists are treating pediatric tumors. Chemotherapy for all pediatric cancers currently is performed at the Pediatric Cancer and Blood Disorders Center of Armenia, established in February 2019 as a result of merging of all pediatric oncology units in the country. Among the 11 practicing pediatric hematologist/oncologists no one is dedicated specifically to PBTs. Since September 2017 we have started discussing all PBT cases (up to now 18 cases) through the telemedicine with St. Jude Children's Research Hospital (SJCRH). In Sept 2019 neuro-oncology multidisciplinary team was created with the involvement of local and foreign specialists. On a weekly basis the multidisciplinary team discusses all new and problematic cases. The team also concentrates on adaptation of diagnostic and treatment guidelines for pediatric CNS tumors, creation of educational materials for different stakeholders, and identification of current problems and their possible solutions. CONCLUSION: To the best of our knowledge this is the first report summarizing the current state of pediatric neuro-oncology in Armenia.